Spontaneous splenic rupture in two patients with hematologic malignancy - Szotkowski, Tomas; Szotkowska, Romana; Pikalova, Zuzana; Tichy, Tomas; Flodr, Patrik; Tichy, Martin; Houserkova, Dana; Benysek, Vladimir; Zlamalova, Nora; Ruzicka, Vaclav; Indrak, Karel (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2007)
BACKGROUND: Spontaneous splenic rupture (SSR) is a very rare complication described in several hundred patients, mainly as case reports. It is defined as a splenic rupture without antecedent injury. The authors of the present paper describe the only two SSR cases diagnosed at the Hemato-oncology department, coincidentally in one year. PATIENTS: The first patient was admitted to hospital because of planned chemotherapy for relapsed hairy cell leukemia. The second was directed to the Hemato-oncology outpatient department because of anemia and painful splenomegaly diagnosed by a physician. The diagnose of hematologic malignancy (diffuse large B-cell lymphoma) was determined subsequently on the basis of histological examination of the spleen. CONCLUSION: It is necessary to consider SSR not only in patients with known diagnosis of malignant disease but in the patients with negative anamnesis, too. The aim of the paper is to draw attention to the existence of this complication.
Keywords: vlasatobuněčná leukemie; Lymphoma, Large B-Cell, Diffuse; ruptura sleziny; Leukemia, Hairy Cell; Adult; dospělí; Humans; mužské pohlaví; Male; lidé; spontánní ruptura; difúzní velkobuněčný B-lymfom; lidé středního věku; Middle Aged; Rupture, Spontaneous; Splenic Rupture